2020
DOI: 10.1016/j.foodchem.2019.125601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of amaranth proteins on the RAS system. In vitro, in vivo and ex vivo assays

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…In these assays, different biological parameters are measured. In the case of antihypertensive peptides, blood pressure and plasma ACE and renin concentrations are measured [230]. Animal models of type 2 diabetes usually reflect insulin resistance and/or beta cell failure.…”
Section: Vertebrates Modelsmentioning
confidence: 99%
“…In these assays, different biological parameters are measured. In the case of antihypertensive peptides, blood pressure and plasma ACE and renin concentrations are measured [230]. Animal models of type 2 diabetes usually reflect insulin resistance and/or beta cell failure.…”
Section: Vertebrates Modelsmentioning
confidence: 99%
“…180 mmHg) began to decrease at 3 h after the administration of either captopril of the hydrolysate, reaching the lowest value after 5 h (110 and 140 mmHg for animals treated with captopril or the hydrolysate, respectively). Suaŕez et al (2020) have recently demonstrated that different products derived from amaranth, a protein isolate, an alcalase hydrolysate, VIKP (a peptide with proven antihypertensive activity, or an oil-water emulsion formulated with isolatehydrolyzed amaranth as a surfactant with and without the addition of VIKP), have antihypertensive activity in SHR. It should be noted that the amount of sample supplied to the animals was 38 times lower in the case of VIKP (50 mg/Kg rat vs 1.9 g protein/Kg rat).…”
Section: In Vivo Assaysmentioning
confidence: 99%
“… Suárez et al. (2020) have recently demonstrated that different products derived from amaranth, a protein isolate, an alcalase hydrolysate, VIKP (a peptide with proven antihypertensive activity, or an oil-water emulsion formulated with isolate-hydrolyzed amaranth as a surfactant with and without the addition of VIKP), have antihypertensive activity in SHR.…”
Section: Bioactive Peptides As Blood Pressure Regulatorsmentioning
confidence: 99%
See 2 more Smart Citations